PAIN IN THE BLADDER - SYMPTOMS, GENERAL INFORMATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The urinary bladder (bladder) is one of the main organs of the body's excretory system; we can say that it functions as a bag for storing fluid. Bladder pain can be caused by many different factors. For example, kidney disease, sexual dysfunction, inflammation in the buttocks. Such pain may indicate the presence of serious diseases not only of the bladder, but also of the organs located next to it.About bladder pain